Two Species Origins Comparison of Herba Patriniae Based on Their Ingredients Profile by UPLC‐QTOF/MS/MS and Orthogonal Partial Least Squares Discriminant Analysis. Issue 9 (31st August 2022) - Su, Dan; Yang, Yanyan; Zeng, Qiang; Liao, Liangliang; Chen, Changlian; Yang, Ming; Zhu, Genhua; Zhang, Ruo‐Wen; Ai, Zhifu; Li, Yanzhen; Song, Yonggui
Abstract: Herba Patriniae (HP) is widely used as a medicinal and edible material in China. Besides food value, HP attracts more attention due to its medicinal potential. Patrinia villosa Juss. ( PV ) and Patrinia scabiosaefolia Fisch. ( PS ) are the two species origins of HP. These two of HP show different effects on cell proliferation, migration, angiogenesis and anti‐diabetic. As we have previously reported, PV and PS show significant differences on their anti‐inflammatory ability in the same experimental model. Comparing the ingredient profiles of two different sources will not only facilitate the understanding of their medicinal effects, but also help the development and research of new activities. However, still now, there is no systematic and detailed study to compare the components of PV and PS . In present study, ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry was employed to achieve a high‐throughput qualitative and thorough analysis of the chemical composition spectrum of HP. A total of 164 compounds were identified, among these compounds, 127 compounds were identified from PV, and 107 compounds were identified from PS . Most of the chemical components was discovered for the first time. Flavonoids, saponins, terpenoids and organic acids, as the main ingredients in PV and PS were 45.45 %vs 28.46 %, 12.61 % vs . 32.09 %, 14.33 % vs . 22.38 % and 14.58 % vs . 6.79 %, respectively. Flavonoids are the main components of PV, while PS is rich in saponins. PV and PS were classified into two groups by principal component analysis (PCA) and screened out the main molecular differences responsible by orthogonal partial least squares discriminant analysis (OPLS‐DA). All the results will be a guide for the quality control, functional activity research, or better clinic use based on the ingredients profile between these two species. Besides, this first study on ingredients profile of two species origins will be beneficial for potential and best resources utilization of both PV and PS . Abstract :